Correlations of Perception Health Service Quality with Adherence Level on Drug Abuse of Inmates in Methadone Clinic, Correctional Institution of Kerobokan - Rachmasari, Ni Made Sri Ayu (Coping: Community of Publishing in Nursing; Vol 1 No 2 (2013): JURNAL EDISI JULI-DESEMBER 2013, 2013)
The development of drug case in Bali is worrying currently ranked 16 throughout nation in terms of circulation and drug abuse. Methadone maintenance therapy is one approach to treatment and rehabilitation of drug addiction by providing methadone in liquid form as a substitute addiction opioida therapy. Methadone treatment is a long-term treatment so patient compliance is crucial for the success of therapy. One factor that may affect compliance with treatment is health service quality and in determining the quality can be assessed through the patients perception. The purpose of this study is to determine the relationship of perception of health service quality to adherence level to drug abuse inmates at Kerobokan Correctional Institution methadone clinic. This research method with non-experimental and data collection done by filling out questionnaire perception of health quality care and medication adherence questionnaire (MMAS). Sample consisted of 20 prisoners selected by the total sampling. Based on data analysis using Rank Spearman obtained results that there is a relationship between the health service quality with level of adherence in methadone clinic of Kerobokan Correctional Institution with Sig 2-tailed value 0.002 and power relations assessed on the value  r=0.645 indicating a strong relationship between two variables. Of the five service quality dimensions showimg reliability, responsiveness, assurance and empathy dimension have a relationship with level of adherence, while the tangible dimension, there is no relationship to the compliance level with drug abuse inmates at Kerobokan Correctional Institution methadone clinic.
Keywords: health service quality, adherence level, prisoners, methadone